If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 = -3x + 10 Reorder the terms: 16 = 10 + -3x Solving 16 = 10 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 16 + 3x = 10 + -3x + 3x Combine like terms: -3x + 3x = 0 16 + 3x = 10 + 0 16 + 3x = 10 Add '-16' to each side of the equation. 16 + -16 + 3x = 10 + -16 Combine like terms: 16 + -16 = 0 0 + 3x = 10 + -16 3x = 10 + -16 Combine like terms: 10 + -16 = -6 3x = -6 Divide each side by '3'. x = -2 Simplifying x = -2
| 3(y-2)=-3(y-3) | | 2x-14=5x+7 | | m^2-75=-11 | | 8x+5y=53 | | -3y(6y+4)+2(3y-10)= | | 19x+13x+7x= | | 20x=2y+10 | | 48x^2-35=0 | | 9x^2-9=-131 | | -3+10=-4 | | (x+23)+(4x+17)+80=180 | | k^4-8=6p | | X+56=64 | | 4x+y+2z=14 | | ((X-3)/(x^2))=((x-3)/(x^2-1)) | | 6x^2+28x-2=0 | | 2(2x+4)=2x+9 | | 17-2=-3 | | 3(2x+6)=4x+3 | | 3(-3)-1/2y=2 | | 3z^2+3=6z | | 3z^2+3=6 | | x^2=725 | | 3(0)-1/2y=2 | | 3(-1)+2y=2 | | 3(-2)-1/2y=2 | | Y-5=0(x+2) | | 6(7x+5)=3x+7 | | 3(7)+Y=51 | | 1.06-3x=.71 | | 3(2x+4)=2(x+4) | | 3(2)-2y= |